2010
DOI: 10.26719/2010.16.5.481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HIV voluntary counselling and testing services in Egypt. Part 1: client satisfaction

Abstract: HIV voluntary counselling and testing (VCT) services were launched in Egypt in 2005. A study of all functioning VCT centres in Egypt (7 mobile and 9 fixed) aimed to determine the profile of clients and their level of satisfaction to identify strengths and weaknesses in the service. In direct interviews with a sample of 928 clients, the main motive for seeking VCT was risky sexual behaviour (34.2%). More females than males sought services because of partners' risky sexual behaviour. More than 90% of the clients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
0
17
1
Order By: Relevance
“…As only four percent respondents knew exactly where to go in case of any grievance this emerged as a factor significantly associated with the satisfaction level of participants. In a study conducted in Egypt, 9 male sex and higher education were associated with higher VCT service satisfaction whereas our study did not find any association between socio-demographics of participants and ICTC service satisfaction. In a study conducted at labs conducting HIV related testing in Tanzania, patients were not satisfied with waiting time, privacy, result notification, cleanliness and timely instructions.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…As only four percent respondents knew exactly where to go in case of any grievance this emerged as a factor significantly associated with the satisfaction level of participants. In a study conducted in Egypt, 9 male sex and higher education were associated with higher VCT service satisfaction whereas our study did not find any association between socio-demographics of participants and ICTC service satisfaction. In a study conducted at labs conducting HIV related testing in Tanzania, patients were not satisfied with waiting time, privacy, result notification, cleanliness and timely instructions.…”
Section: Discussioncontrasting
confidence: 51%
“…10 A study from Egypt reported that more than 90% of clients were satisfied with the voluntary counselling and testing (VCT) services. 9 In the present study, signage display emerged as a weakness as 90% respondents said that there were not enough signage to guide patients to the ICTC. However study didn't find any association between "information, access and guidance for services" and the difference in level of ICTC client satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study reported that 95% of end users receiving ART who participated in the study thought that the counselling sessions were good, and indicated knowledge gained and increased hope and the ability to make informed choices. [17][18][19][20][21][22][23] In addition to counselling, end users wanted to be assessed and have the assessment results properly communicated to them. This relates to strengthening internal systems to ensure that end users are routinely provided with basic assessments whenever they present for care in health facilities.…”
Section: Discussionmentioning
confidence: 99%